ANALYSIS OF THE INFLUENCE OF WFA WORK METHODS AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. SEPULSA TECHNOLOGY INDONESIA - Yune Ilhami; Okder Pendrian (Jurnal Ekonomi, 2023)
The Covid-19 pandemic has had a significant impact on the global business order, including in Indonesia. To be able to maintain its existence and continue to grow, companies in Indonesia have implemented several strategic initiatives, including implementing the work from home method. PT. Sepulsa Teknologi Indonesia also implemented the same work method which eventually developed into work from anywhere. The purpose of this study was to analyze how the influence of the application of the WFA work method and the level of work motivation on employee performance. The research was conducted using a quantitative method by distributing questionnaires which were attended by 154 respondents. The results of the study show that the application of the WFA method does not have a significant effect on employee performance but instead provides other benefits in terms of cost efficiency and also time efficiency for both employees and the company. Besides that, the application of the WFA work method has an influence on employee motivation.